Mechanically stable antimicrobial chitosan-PVA-silver nanocomposite coatings deposited on titanium implants - Mishra, Sandeep K
Bionanocomposite coatings with antimicrobial activity comprising polyvinyl alcohol (PVA)-capped sil-ver nanoparticles embedded in chitosan (CS) matrix were developed by a green soft chemistry synthesisroute. Colloidal sols of PVA-capped silver nanoparticles (AgNPs) were synthesized by microwave irradi-ating an aqueous solution comprising silver nitrate and PVA. The bionanocomposites were prepared byadding an aqueous solution of chitosan to the synthesized PVA-capped AgNPs sols in appropriate ratios.Uniform bionanocomposite coatings with different contents of PVA-capped AgNPs were deposited ontotitanium substrates by “spread casting” followed by solvent evaporation. Nanoindentation and antimicro-bial activity tests performed on CS and bionanocomposites revealed that the incorporation of PVA-cappedAgNPs enhanced the overall functional properties of the coatings, namely their mechanical stability andbactericidal activity against Escherichia coli and Staphylococcus aureus. The coated specimens maintainedtheir antimicrobial activity for 8 h due to the slow sustained release of silver ions. The overall benefitsfor the relevant functional properties of the coatings were shown increase with increasing contents ofPVA-capped AgNPs in the bionanocomposites